Domain stability of PbTiO3 thin films under anisotropic misfit strains: Phase-field simulations - Sheng, G.; Zhang, J. X.; Li, Y. L.; Choudhury, S.; Jia, Q. X.; Liu, Z. K.; Chen, L. Q. (Journal of applied physics, 2008)
The domain stability and domain structures of (001)-oriented PbTiO3 ferroelectric thin films subject to anisotropic in-plane strains were studied using phase-field method. Based on the simulation results, a room temperature domain/phase stability diagram was constructed for PbTiO3 thin films with the in-plane strains ranging from −5% to 5%. The predicted diagram is both quantitatively and qualitatively different from those obtained using thermodynamic calculations based on a single-domain assumption.